TINGKAT PENGETAHUAN DAN PEMAHAMAN MASYARAKAT TENTANG PENGGUNAAN OBAT YANG BENAR DI KOTA KUPANG TAHUN 2014 - JEFRIN SAMBARA; NI NYOMAN YULIANI; YANTRI BURENI (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Medication is the primary requirement for being sick. When given the proper dosage can cure disease, relieve pain, and can improve human health. However, if not used appropriately and correctly will worsen the condition of patients with pain. Improper use of the drug can occur due to lack of knowledge and understanding of the correct use of medications. Therefore, the authors are interested in doing research with the title